Lateral Flow Test (LFT) Detects Cell‐Free MicroRNAs Predictive of Preterm Birth Directly from Human Plasma. Issue 9 (16th June 2022) - Petrou, Loukia; Latvanen, Elmeri; Seichepine, Florent; Kim, Sung Hye; Bennett, Phillip R.; Sykes, Lynne; MacIntyre, David A.; Terzidou, Vasso; Ladame, Sylvain
Abstract : Despite extensive research toward the development of point‐of‐care nucleic acid tests (POC NATs) for the detection of microRNAs (miRs) from liquid biopsies, major hurdles remain including the strict requirement for extensive off‐chip sample preprocessing. Herein, a nucleic acid lateral flow test (NALFT) is reported on that enables the direct detection of endogenous miRs from as little as 3 μL of plasma without the requirement for any enzyme‐catalyzed target amplification or complex miR extraction steps. This is achieved through integration of a denaturing hydrogel composite material onto the LFT, allowing for near‐instantaneous on‐chip release of miRs from their carriers (extracellular vesicles or transport proteins) prior to detection. This next‐generation LFT is sensitive enough to detect endogenous concentrations of miR‐150‐5p, a predictive biomarker for preterm birth (PTB) found deregulated in maternal blood from as early as 12th week of pregnancy. Herein, a key step is represented toward a first bedside test for risk‐stratification during pregnancy by predicting true outcome at a very early stage. More generally, the universal and versatile nature of this novel sample preprocessing platform can further improve the robustness of existing NALFTs and facilitate their application at the POC. Abstract : On‐chip microRNA release from carrier protein and extracellular vesicles using a denaturing hydrogel–cellulose pad enables direct detection of predictive circulating microRNA biomarkers for preterm birth directly from human plasma. This next‐generation bedside lateral flow test provides a unique tool for risk‐stratification during pregnancy by predicting true outcome at a very early stage.